Antiplatelet therapy: a double-edged sword in head injury? - Beynon, Christopher; Sakowitz, Oliver (Critical care, 2013)
Antiplatelet therapy for the treatment of cardiovascular diseases is common in the ageing population. Whether this therapy exacerbates brain injury after head trauma is an important, but unsettled, topic. In this issue of Critical Care, Fabbri and colleagues address the question of whether pre-injury intake of antiplatelet medication increases the risk profile of patients with posttraumatic intracranial lesions after head trauma. Antiplatelet medication, and in particular clopidogrel, increased the risk for haematoma progression, need for neurosurgical intervention and an unfavourable outcome. Clinicians should consider this increased risk profile in the treatment of respective patients. Since its introduction as an analgesic in 1897, aspirin has surprised the medical community more than once due to its versatile properties. Prevention of secondary brain damage through aspirin has been reported for ischaemic stroke and subarachnoid haemorrhage. In cases of acute traumatic haemorrhage after head injury, antiplatelet therapy's neuroprotective effects may be outweighed by the increased bleeding tendency.
Gesehen am 25.11.2020